TERTIARY EDUCATION AND ECONOMICS REFORM OF SUBSIDY REMOVAL IN NIGERIA: IMPLICATION FOR EDUCATIONAL ADMINISTRATION AND PLANNING - Kemeasuode, Egirigi; Onome, Amukoyo; Ifeanyi, Anene Cyril (Journal of Social Science, 2026)
Objective: This study investigates the financial implications and tertiary education reforms resulting from Nigeria’s removal of educational subsidies, focusing on its effects on the management and governance of educational institutions. Method: Using a quantitative research design, the study analyzes data collected from surveys, academic journals, and government reports to assess both the benefits and challenges associated with subsidy removal. Results: The findings reveal that while the removal of subsidies has increased government funding for education, improved infrastructure, enhanced teacher welfare, and supported Sustainable Development Goals (SDGs), it has also led to higher school fees, increased dropout rates, reduced support for low-income families, and widened inequalities in educational access. Novelty: This research contributes to policy discourse by emphasizing the need for a legal framework to allocate a portion of subsidy savings directly to educational development—particularly in infrastructure, research, and teacher training—and by proposing mitigation strategies such as school feeding programs, scholarships, and free learning materials to cushion the socioeconomic impact of subsidy removal.